A High-Fat Diet Induces Low-Grade Cochlear Inflammation in CD-1 Mice - Jeffrey Chan (International Journal of Molecular Sciences, 2022)
There is growing evidence for a relationship between gut dysbiosis and hearing loss. Inflammatory bowel disease, diet-induced obesity (DIO), and type 2 diabetes have all been linked to hearing loss. Here, we investigated the effect of a chronic high-fat diet (HFD) on the development of inner ear inflammation using a rodent model. Three-week-old CD-1 (Swiss) mice were fed an HFD or a control diet for ten weeks. After ten weeks, mouse cochleae were harvested, and markers of cochlear inflammation were assessed at the protein level using immunohistochemistry and at the gene expression level using quantitative real-time RT-PCR. We identified increased immunoexpression of pro-inflammatory biomarkers in animals on an HFD, including intracellular adhesion molecule 1 (ICAM1), interleukin 6 receptor α (IL6Rα), and toll-like-receptor 2 (TLR2). In addition, increased numbers of ionized calcium-binding adapter molecule 1 (Iba1) positive macrophages were found in the cochlear lateral wall in mice on an HFD. In contrast, gene expression levels of inflammatory markers were not affected by an HFD. The recruitment of macrophages to the cochlea and increased immunoexpression of inflammatory markers in mice fed an HFD provide direct evidence for the association between HFD and cochlear inflammation.